Antecedents of banks’ productivity growth in a developing economy: efficiency change or technological progress? - Sufian, Fadzlan (Inderscience Publishers, 2010)
This paper attempts to empirically analyse the Malaysian banking sector’s productivity during the period 1995–2004. The empirical findings suggest that the Malaysian banking sector has exhibited productivity regress during the period under study mainly due to technological regress, rather than efficiency decline. The results suggest that the domestic banks’ productivity were almost stagnant, while the foreign banks have exhibited productivity decline. The relationship between different bank size and productivity indicates that the majority of Malaysian banks which experienced productivity growth were the medium and large banks group, while the majority of banks that experienced productivity regress belonged to the small banks group.